Prematuridade: implicações e riscos para o desenvolvimento na primeiríssima infância, da avaliação à intervenção - Cavaggioni, Ana Paula Magosso (2022)
The national and international literature indicates that there is a greater risk of delays in the development of premature babies when compared to full-term babies, which can cause lifelong losses. Even so, public policies that guarantee care for this population are scarce and, when they exist, cover only those who need hospitalization in a Neonatal Intensive Care Unit. Those who are born apparently healthy are neglected. The present study aimed to 1) Describe and relate the areas of development of children born prematurely; 2) Describe and compare the performance of children according to the gestational age at birth: very preterm, moderate preterm, and late preterm, and 3) Identify, through a case study, areas of competence and lag of a premature child. Participants were 79 children aged 15 days to 42 months, whose development in Cognition, Language, and Motor was assessed by the Bayley Infant and Toddler Development Scale - III). Additionally, mothers completed a sociodemographic questionnaire and the Bayley III Adaptive and Socioemotional Behavior Scales. The babies were divided into three groups according to gestational age: very preterm, moderate preterm, and late preterm. The quantitative data received descriptive and inferential statistical treatment. The quantitative analysis encompassed the developmental outcomes of the babies, in terms of means and standard deviation of the weighted, composite, and percentile scores, taking into account both the total sample and the comparison between groups. A qualitative analysis was also carried out, which consisted of a case study. The results showed that, in general, all participants performed as expected in the weighted, composite, and percentile scores in the Bayley-III Scale domains. However, about 39% of participants did not achieve complete acquisition in Sensory Processing. Furthermore, 50.6% of them showed at least one statistically significant discrepancy when comparing two areas of development. In the comparison between groups, 50% of moderate preterm and 41% of late preterm infants did not achieve complete acquisition of Sensory Processing, and a statistically significant difference was found in Socioemotional between them. In the comparison between Domains, there was a statistically significant difference in Cognitive-Socio-emotional, (p=.01) and in Gross Motor-Socio-emotional (p=.03). The qualitative analysis indicated the need to monitor the development of healthy preterm infants with a discrepant developmental profile between the domains and the involvement of family, school, and health professionals, since even apparently healthy children have subtle deficits that can affect school age and age. adulthood. Although the findings of the present research indicate adequate development of preterm infants in all Domains, the presence of a high frequency of significant discrepancies between them, when comparing their results with each other, pointed to a disharmonious development, which, in the long term, can cause negative consequences. in the life of this population, as widely reported in the literature. Therefore, the importance of monitoring premature infants in very early childhood and the development of effective public policies that include even those who do not need special medical care at birth becomes evident.(AU)